2005
DOI: 10.1103/physrevlett.94.178102
|View full text |Cite
|
Sign up to set email alerts
|

Optical Conductivity of Wet DNA

Abstract: Motivated by recent experiments, we study the optical conductivity of DNA in its natural environment containing water molecules and counterions. Our density functional theory calculations (using Siesta) for four base pair B-DNA with order 250 surrounding water molecules suggest a thermally activated doping of the DNA by water states which generically leads to an electronic contribution to low-frequency absorption. The main contributions to the doping result from water near DNA ends, breaks, or nicks and are th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
69
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 25 publications
9
69
2
Order By: Relevance
“…The figure demonstrates that the counterions (green curve) indeed contribute new empty electron states in the gap between the G (∼−0.5 eV) and the C (∼2 eV) peaks, with a very low DOS relative to the G and C features, yet a finite number of discrete levels scattered throughout the G-C gap and roughly centred around 1 eV. Let us now discuss why the Na + levels, which are a direct output of our calculations, may help explain the observations, contrary to unsatisfactory attempts that are based only on the ground-state electronic structure on G and C. Ab initio DFT electronic structure calculations of G-rich DNA polymers usually report a π-π * G-C energy gap of ∼2−3 eV, depending on the exact polymer sequence and computational details 23,24,30,31 , consistent with our findings. Taking into account that ground-state DFT results underestimate the gap between occupied and unoccupied states by as much as 100% and even more, the measurement of an average fundamental gap of ∼2.5 eV (Table 1) cannot be explained naively in terms of a G-C gap, because the theoretical prediction should be shifted to roughly 5-6 eV.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The figure demonstrates that the counterions (green curve) indeed contribute new empty electron states in the gap between the G (∼−0.5 eV) and the C (∼2 eV) peaks, with a very low DOS relative to the G and C features, yet a finite number of discrete levels scattered throughout the G-C gap and roughly centred around 1 eV. Let us now discuss why the Na + levels, which are a direct output of our calculations, may help explain the observations, contrary to unsatisfactory attempts that are based only on the ground-state electronic structure on G and C. Ab initio DFT electronic structure calculations of G-rich DNA polymers usually report a π-π * G-C energy gap of ∼2−3 eV, depending on the exact polymer sequence and computational details 23,24,30,31 , consistent with our findings. Taking into account that ground-state DFT results underestimate the gap between occupied and unoccupied states by as much as 100% and even more, the measurement of an average fundamental gap of ∼2.5 eV (Table 1) cannot be explained naively in terms of a G-C gap, because the theoretical prediction should be shifted to roughly 5-6 eV.…”
mentioning
confidence: 91%
“…4a). We are aware that the solvent may also play a role in pinning the electron levels, but this issue is still controversial and is addressed elsewhere 31,32 , and it is not expected to compromise the essence of our results (see the discussion on the water effects in the Supplementary Information). Previous similar simulations were done for the same poly(G)-poly(C) sequence without including the counterions 23 : it was found that the fundamental bandgap is only due to the guanine (G) and cytosine (C) bases.…”
mentioning
confidence: 99%
“…The presence of these small activation energies in the electronic structure brings an additional mechanism in order to explain the anomalous absorption feature observed at low ͑10-100 meV͒ energies in optical conductivity spectra of biological DNA samples. 53,54 Some words regarding the possible effect of the watercounterions surrounding on the collective twist motion of bps are in order. Broadly speaking these effects are twofold.…”
Section: Discussionmentioning
confidence: 99%
“…Both ab initio calculations [14][15][16][17][18][19][20][21][22][23] as well as model-based Hamiltonian approaches [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] have been recently discussed. Though the former can give in principle a detailed account of the electronic and structural properties of DNA, the huge complexity of the molecule and the diversity of interactions present in it ͑internal as well as with the counterions and hydration shells͒ precludes a full systematic first-principles treatment of electron transport for realistic molecule lengths, this becoming even harder if the dynamic interaction with vibrational degrees of freedom is considered.…”
Section: Introductionmentioning
confidence: 99%